English Students' Perception and Motivation on Online Learning: A Descriptive Study on English Language Education Master Program Students FKIP Untan in the Academic Year 2022/2023 - Wiranto, Irfan Agung (Jurnal Alwatzikhoebillah : Kajian Islam, Pendidikan, Ekonomi, Humaniora, 2024)
Online learning has become essential since the beginning of the COVID-19 pandemic, especially in the educational environment. The aim of this study was to find out students’ perception and motivation on online learning. This research was qualitative study. The subject of this study was the third and fifth semester students from the S2 English Language Education study program in Teacher Training and Education Faculty at Universitas Tanjungpura Pontianak. In order to collect the data, both questionnaire and interview were applied. The result showed the majority of students have a positive view on online learning during the pandemic. However, some students had negative perceptions of online learning due to poor internet connections and miscommunications that occurred while learning online. Moreover, almost all students were intrinsically motivated during the process of online learning.